PHENOMENOLOGY OF TREMOR-LIKE SIGNALS OBSERVED OVER HYDROCARBON RESERVOIRS - Dangel S.; Schaepman M.E.; Stoll E.P.; Carniel R.; Barzandji O.; Rode E.-D.; Singer J.M. (My University, 2003)
We have observed narrow-band, low-frequency (1.5–4 Hz, amplitude 0.01–10 μm/s) tremor signals on the surface over hydrocarbon reservoirs (oil, gas and water multiphase fluid systems in porous media) at currently 15 sites worldwide. These ‘hydrocarbon tremors’ possess remarkably similar spectral and signal structure characteristics, pointing to a common source mechanism, even though the depth (some hundreds to several thousands of meters), specific fluid content (oil, gas, gas condensate of different compositions and combinations) and reservoir rock type (such as sandstone, carbonates, etc.) for each of those sites are quite different. About half of the sites are fully explored or even developed and producing fields, and hard quantitative data on the reservoirs are available (well data, reservoir monitoring data, seismic surveys, etc.). The other areas are essentially either explored prospect areas where we did not have access to hard reservoir data or (in only one case) areas where no exploration wells have been drilled at all. The tremor signal itself was observed over ALL locations investigated so far. The signals weaken at the rim of the reservoirs and are not observed outside the reservoir area. There is a strong correlation of the tremor power with the thickness of the hydrocarbon-bearing layers (‘pay zone thickness’) determined by borehole log measurements. The overall correlation between surface tremor measurements and accessible subsurface well data is higher than 90%. The phenomenological comparison of hydrocarbon tremor signals with volcanic tremor signals from Stromboli and Arenal volcanoes using both conventional spectral analysis tools and non-linear dynamics methods reveals fundamental similarities between those two phenomena as well as their close relation to bandpass filtered noise. Nevertheless, the specific signal sources are expected to be different for volcanoes and hydrocarbon reservoirs. Using the currently available data we present possible concepts (active or passive mechanisms) on the nature of the hydrocarbon tremor source. Our data lead us to conclude that we are most likely observing a characteristic filtering/mixing effect, with the energy input supplied by the natural seismo-acoustic background. The reservoir, i.e. the hydrocarbon-water-multifluid system contained in a porous medium, is expected to be the oscillatory element able to act as a filter/mixer (resembling essentially a in-reservoir path effect) for the natural seismo-acoustic background. Most intriguing seems the application aspect, i.e. the practical usability of this spectroscopic approach as a direct from-the-surface, non-invasive hydrocarbon indicator.
Keywords: volcanic tremor; spectral analysis; hydrocarbon reservoir; nonlinear time series analysis; seismic background noise